(untitled) (Bangladesh Journal of Botany, 2022)
Fusarium fujikuroi, the causal agent of foot rot disease, infects all the parts of rice, causing serious yield losses in different parts of the world. In order to understand the basis of disease tolerance, various biochemical and anatomical traits of ten days old healthy and infected basmati and non-basmati rice seedlings were compared. Total soluble sugar content was higher in healthy seedlings, while total phenols, orthodihydroxy phenols and total soluble proteins were higher in non-basmati rice seedlings post infection indicating the initiation of defence against the pathogen. Increase in the total antioxidant activity, enzymes and α-tocopherols in basmati rice cultivars post infection indicate the oxidative stress created by pathogen. Histopathological observations revealed hyphal and conidial growth in infected tissues of basmati cultivars whereas a complete and intact tissue was observed in healthy and infected counterparts of non-basmati cultivars. Bangladesh J. Bot. 51(1): 29-36, 2022 (March)